2023
DOI: 10.3389/fnut.2023.1118761
|View full text |Cite
|
Sign up to set email alerts
|

New insights of the application of water or ethanol-water plant extract rich in active compounds in food

Abstract: Plants are recognized as natural sources of antioxidants (e.g., polyphenols, flavonoids, vitamins, and other active compounds) that can be extracted by green solvents like water, ethanol, or their binary mixtures. Plant extracts are becoming more used as food additives in various food systems due to their antioxidant abilities. Their application in food increases the shelf life of products by preventing undesirable changes in nutritional and sensory properties, such as the formation off-flavors in lipid-rich f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 229 publications
0
13
0
Order By: Relevance
“…In the case of less polar molecules, a higher efficiency can be achieved with the aid of organic solvents. The most satisfactory results are usually obtained with binary solvent mixtures (e.g., water and an organic solvent), which also have been shown to be more efficient and environmentally friendly than pure organic solvents [ 11 ]. In order to improve the effectiveness of the bioactive substance extraction, aqueous/organic solvents must be combined at the appropriate ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of less polar molecules, a higher efficiency can be achieved with the aid of organic solvents. The most satisfactory results are usually obtained with binary solvent mixtures (e.g., water and an organic solvent), which also have been shown to be more efficient and environmentally friendly than pure organic solvents [ 11 ]. In order to improve the effectiveness of the bioactive substance extraction, aqueous/organic solvents must be combined at the appropriate ratio.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that less polar flavonoids, such as flavanones, flavanols, isoflavones and methylated flavones are more soluble in ethyl acetate, diethyl ether, chloroform and dichloromethane. However, due to the toxicity of these solvents, they must be handled with caution and need to be evaporated to a safe limit permissible for food [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a certain variability on the bioactivity level of the hibiscus extracts is expected, depending on the selected solvent. In the current study was used ethanol since it is considered a green solvent, i.e., it is safe, non-toxic and presents a low environmental risk [56]. Moreover, ethanol has been proving enhanced effectiveness to extract compounds with antimicrobial activity, as compared to other solvents, such as methanol and acetone [57].…”
Section: Discussionmentioning
confidence: 99%
“…This efficiency may be due, on the one hand, to the nature of the solvents and the extraction method. Many active constituents were easily extractable in water [39].…”
Section: Discussionmentioning
confidence: 99%